Integrating augmented reality storytelling into early childhood mathematics: design, validation, and effectiveness of a marker based interactive e-book - Sihombing, Sri Cahaya; Utoyo, Setiyo; Rakimahwati; Mahyuddin, Nenny (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aimed to develop and evaluate an Augmented Reality (AR) marker based interactive picture story e-book designed to enhance early childhood mathematical abilities. Method: A Research and Development (R&D) approach was employed using the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The study involved 28 children aged 5 6 years. The development process began with a needs analysis to identify gaps in existing instructional practices. The e-book incorporated key mathematical domains, including number concepts, patterns, geometry, measurement, and simple data representation, supported by AR visualization and interactive activities. Content validity was assessed by media, material, and early childhood mathematics experts. Practicality was examined through small and large group trials, while effectiveness was measured using a one-group pretest posttest design analyzed with the Wilcoxon Signed Ranks Test and N-gain score calculation. Findings: The needs analysis revealed a high demand for interactive digital mathematics media (89.8%). Expert validation indicated high validity levels, and practicality testing demonstrated strong usability. Statistical analysis showed a significant improvement in children’s mathematical abilities (p < .05), with a high N-gain score (0.70). Significance: The findings suggest that AR integrated storytelling provides an effective and engaging approach to strengthening early mathematical competencies within technology-enhanced learning environments.